Les dents de la nuit = Vampire party [videorecording (DVD)] - Benes, Jean-Patrick; Mauduit, Alan; Delaporte, Matthieu; La Patellière, Alexandre de, 1971-; Cafiero, Stephen; Lobelle, Vincent; Gauquie, David; Ben Youssef, Walid; Ganay, Thierry de; Mille, Patrick; Bel, Frédérique; Fournier, Julie; et al. (Dark Sky Films, 2008)
Hardcore partiers Sam, Alice, and Prune have scored invitations to a legendary VIP bash, but discover that it's being thrown by a race of blood-crazed vampires. Now, they are going to have to stake, stab, slice, bludgeon and blast their way out of a soiree where the hosts are thirsty and the bar is now open.